2016
DOI: 10.1007/s13277-016-5434-y
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression profile of infantile hemangioma identified by microarray analysis

Abstract: Infantile hemangioma (IH) is one of the most common vascular tumors of childhood. Long noncoding RNAs (lncRNAs) play a critical role in angiogenesis, but their involvement in hemangioma remains unknown. This study aimed to assess the expression profiles of lncRNAs in IH and adjacent normal tissue samples, exploring the biological functions of lncRNAs as well as their involvement in IH pathogenesis. The lncRNA expression profiles were determined by lncRNA microarrays. A total of 1259 and 857 lncRNAs were upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 60 publications
0
39
2
Order By: Relevance
“…Their qRT‐PCR and transwell assay results indicated that the knockdown of linc00152 prevents PDAC cell proliferation and invasion, thereby verifying the oncogenic property of linc00152. The involvement of linc00152 in cell proliferation has also been confirmed in gastric cancer, hepatocellular carcinoma (HCC), pancreatic cancer, clear cell renal cell carcinoma, colorectal cancer, breast cancer, and infantile hemangioma …”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Their qRT‐PCR and transwell assay results indicated that the knockdown of linc00152 prevents PDAC cell proliferation and invasion, thereby verifying the oncogenic property of linc00152. The involvement of linc00152 in cell proliferation has also been confirmed in gastric cancer, hepatocellular carcinoma (HCC), pancreatic cancer, clear cell renal cell carcinoma, colorectal cancer, breast cancer, and infantile hemangioma …”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 92%
“…The involvement of linc00152 in cell proliferation has also been confirmed in gastric cancer, [25][26][27][28][29][30][31][32] hepatocellular carcinoma (HCC), 11,20 pancreatic cancer, 33 clear cell renal cell carcinoma, 34 colorectal cancer, 35 breast cancer, 36 and infantile hemangioma. 37 Cao et al 26 applied a cDNA microarray to analyze the profiles of differentially expressed lncRNAs in 88 gastric cancer tissue samples and paired adjacent normal tissues. They detected 80 kinds of differentially expressed lncRNAs, of which the expression levels of linc00152 were particularly significantly different.…”
Section: Overexpression Of Linc00152 Enhances Cell Proliferation Imentioning
confidence: 99%
“…Abnormal expression of lncRNAs is involved in the pathogenesis of various diseases. In recent years, many studies have used microarray technology to screen for differentially expressed lncRNAs in the occurrence of disease . Exploring the mechanism of disease regulation or new mechanisms have become common practice.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of MEG3 acts as an independent factor for predicting poor prognosis in cancer patients [12,15,25,26], and the downregulation of MEG3 is attributed to its promoter hypermethylation in cancer [27][28][29], and the negative modulation by DNMT1 in glioma [30]. MEG3 and VEGF have the differential expression levels in HAs [5,18]. In the present study, we found that, MEG3 expression was decreased and harbored the negative association with VEGF expression in proliferating phase HAs rather than in the involuting phase HAs, suggesting that MEG3 might be a negative regulator of HAs proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA expression profiles have been used to identify the involvement of MEG3 in the pathogenesis of Infantile HAs [18]. In addition to the lncRNAs, microRNAs (miRNAs), a subgroup of ncRNAs with about 20 nucleotides that inhibit their target gene are differentially expressed in different phase HAs [19].…”
Section: Introductionmentioning
confidence: 99%